Eosinophilic esophagitis: dilate or medicate? A cost analysis model of the choice of initial therapy. Issue 5 (4th September 2012) - Kavitt, R. T.; Penson, D. F.; Vaezi, M. F.
Summary Eosinophilic esophagitis (EoE) is an increasingly recognized clinical entity. The optimal initial treatment strategy in adults with EoE remains controversial. The aim of this study was to employ a decision analysis model to determine the less costly option between the two most commonly employed treatment strategies in EoE. We constructed a model for an index case of a patient with biopsy‐proven EoE who continues to be symptomatic despite proton‐pump inhibitor therapy. The following treatment strategies were included: (i) swallowed fluticasone inhaler (followed by esophagogastroduodenoscopy [EGD] with dilation if ineffective); and (ii) EGD with dilation (followed by swallowed fluticasone inhaler if ineffective). The time horizon was 1 year. The model focused on cost analysis of initial treatment strategies. The perspective of the healthcare payer was used. Sensitivity analyses were performed to assess the robustness of the model. For every patient whose symptoms improved or resolved with the strategy of fluticasone first followed by EGD, if necessary, it cost an average of 1078. Similarly, it cost an average of 1171 per patient if EGD with dilation was employed first. Sensitivity analyses indicated that initial treatment with fluticasone was the less costly strategy to improve dysphagia symptoms as long as the effectiveness of fluticasone remains at or above 0.62. Swallowed fluticasone inhaler (followed by EGD with dilation if necessary) is the more economical initial strategy when compared with EGD with dilation first.